Factors of Promoting Agro-Tourism during the Crisis COVID-19 in Rayong - Aranyapruk, Obrom (Journal of Management Science Chiangrai Rajabhat University, 2023)
This research has the following objectives 1) To study the agritourism behavior of Thai tourists in Rayong Province 2) To study the factors promoting agritourism during the COVID-19 crisis in Rayong Province 3) To compare the factors promoting tourism. Agriculture during the COVID-19 crisis in Rayong Province was classified by general status including gender, age, status, monthly income and occupation. By using a survey research method. Data was collected from 222 people in Rayong Province by using both descriptive statistics and inferential statistics. The tool used is a questionnaire. Data were analyzed using a simple random sampling method. There is a calculation to find the confidence value of the questionnaire. (Reliability) using the alpha coefficient analysis method. Get a value equal to 0.965. The results showed that most of the samples were female, single, with a monthly income not exceeding 15,000 Baht, and identified their occupation as a secondary student or college student. The overall results of analyzing factors in promoting agro-tourism during the COVID-19 crisis in Rayong Province as a whole. It was found that the personnel aspect was at a high level followed by ‘measures to prevent COVID-19, location and information’, respectively. The results of the analysis in each item found that ‘beautiful scenery’ was of the highest level of importance. The differential comparison between the average factors promoting agro-tourism during the Covid -19 crisis, gender, age, status and income were not significantly different at the .05 level. In the overview, only occupations were found to be significantly different at .05 in each item. In terms of age, it was found that there were 5 items of significant difference at the .05 level. In terms of status, it was found that there were 2 items of significant difference at the .05 level. There were 5 items of statistically significant difference at the .05 level, and 7 items of occupation were found to have statistically significant differences.